Time budgets and at-sea behaviour of lactating female Antarctic fur seals Arctocephalus gazella at Bouvetøya - Biuw, Martin; Krafft, Bjørn A.; Hofmeyr, G. J. Greg; Lydersen, Christian; Kovacs, Kit M. (Marine ecology. Progress series, 2009)
We present the first data on attendance patterns, at-sea movements and diving behaviour of Antarctic fur seals breeding at Bouvetøya (Bouvet Island), Southern Ocean. While other colonies have been extensively studied, this remote and second largest global population remains relatively unknown. Time depth recorders and satellite relay data loggers were deployed on breeding females during the 2000–2001 and 2001–2002 summers. Attendance and foraging patterns were similar to those observed at colonies in the Scotia Sea region where Antarctic krill is the predominant prey. Early to mid-lactation trips ranged within ~100 km of the island, usually towards the west. The dominant direction shifted later in the season and the range also increased markedly to a peak between early February and early March. Solar elevation influenced arrivals and departures from the island, with most departures occurring around sunset. Diurnal variations in diving behaviour were consistent with the vertical migration of krill. Diving frequency was higher at night and diving effort peaked around morning twilight. Afternoon deep diving was common, suggesting that females might target dense daytime krill aggregations between the photic zone and the thermocline. Trip durations increased throughout early to mid-lactation, peaking in late January to early March, before again decreasing towards the end of lactation. Our results illustrate the substantial variability, both between individuals and within individuals over time, that is likely to reflect variations in prey distribution and in the growth requirements of pups. Such variations need to be taken into account when estimating habitat use and resource utilisation in marine top predators.
Keywords: Bouvetøya; krill; marin biologi; pelsseler; plankton; satellittsendere; zoologi; økologi

Biologging in the Global Ocean Observing System - Boehme, Lars; Kovacs, Kit M; Lydersen, Christian; Nøst, Ole Anders; Biuw, Martin; Charrassin, Jean-Benoît; Roquet, Fabien; Guinet, Christophe; Meredith, Michael; Nichols, K; Thorpe, Sally; Costa, Daniel; et al. (Proceedings of Ocean Obs 09: Sustained ocean observations and information for society, Venice, Italy, European Space Agency, 2009)
Miniature electronic data recorders and transmitters have revolutionized the way we study animals over the past decades, particularly marine animals at sea. But, very recently, animal-borne instruments have also been designed and implemented that provide in situ hydrographic data from parts of the oceans where little or no other data are currently available (even from beneath the ice in polar regions). Ocean data is delivered from animal-borne instruments via satellites in near real-time, which would enrich the Global Ocean Observing System if animal-borne instruments were deployed systematically. In the last 10 years, studies involving more than 10 countries (Australia, Brazil, Canada, France, Germany, Greenland, Norway, South Africa, UK, USA) have demonstrated how highly accurate oceanographic sensors, integrated into standard animal, biologging instruments, can provide data of equal or better quality than XBT/XCTD data. Here, we present some of the pioneering studies and demonstrate that we now have enough information for many marine species to predict where they will go – within reasonable limits. Thus, we can direct sampling effort to particularly interesting and productive regions and maximize data return. In the future, biologging could certainly play an important part in the Global Ocean Observing System, by providing complementary data to more traditional sampling technologies - especially in the high latitudes. This paper will make a core contribution to the Plenary Sessions 4A, 4B and 5A and will be relevant to 2A, 2B and 3A.
Keywords: Bouvetøya; Sørishavet; biologging; marin biologi; oseanografi

New insights into southern ocean physical and biological processes revealed by instrumented elephant seals - Charrassin, Jean-Benoît; Roquet, Fabien; Park, Young-Hyang; Bailleul, Frédéric; Guinet, Christophe; Meredith, Michael; Nicholls, K; Thorpe, Sally; McDonald, Birgitte; Costa, Daniel; Tremblay, Yann; Goebel, Michael; et al. (Proceedings of Ocean Obs 09: Sustained ocean observations and information for society, Venice, Italy, European Space Agency, 2009)
In recent years, the international “Southern Elephant seals as Oceanographic Samplers” (SEaOS) project has deployed miniaturized conductivity-temperature-depth satellite-relayed data loggers (CTD-SRDL) on elephant seals 1) to study their winter foraging ecology in relation to oceanographic conditions, and 2) to collect hydrographic data from polar regions, which are otherwise sparsely sampled. We summarize here the main results that have been published in both science components since 2003/2004. Instrumented southern elephant seals visit different regions within the Southern Ocean (frontal zones, continental shelf, and/or ice covered areas) and forage in a variety of different water masses (e.g. Circumpolar Deep Water upwelling regions, High Salinity Shelf Water), depending on their geographic distribution. Adult females and juvenile males from Kerguelen Is. forage pelagically in frontal zones of the Southern Indian Ocean, while adult males forage benthically over the Kerguelen Plateau and the Antarctic Continental Shelf, with the two groups feeding at different trophic levels as shown by stable isotopes analysis. Oceanographic studies using the data collected from the seals have, to date, concentrated on circumpolar and regional studies of the Antarctic Circumpolar Current (ACC) circulation. The temperature and salinity profiles documented by elephant seals at high latitudes, including below sea ice, have permitted quasi-circumpolar mapping of the southernmost fronts of the ACC. By merging conventional data and the high temporal and spatial resolution data collected by seal-borne SRDLs, it has been possible to describe precisely 1) the large-scale features of the ACC in the South Atlantic and its variability; 2) the circulation pattern over the Kerguelen plateau, revealing that the poorly known Fawn Trough concentrates an important proportion of the ACC flow in that region. Seals that foraged in ice covered areas have made eulerian time series available that have allowed for the estimation of sea ice formation rates, a parameter that is otherwise difficult to obtain, while also providing a unique description of the wintertime ocean circulation over the central Weddell Sea continental shelf. Finally, we present the first data collected by a newly-developed fluorescence sensor that as been embedded in the regular CTD-SRDL and deployed on elephant seals at Kerguelen. The fluorometer data obtained have offered the first synoptic view of the 3 dimensional distribution of temperature, salinity and fluorescence over a vast sector of the Southern Indian Ocean, allowing us to describe both vertical and horizontal variations in chlorophyll. This paper will make a core contribution to the Plenary Sessions 2C, 3A and 4A, and will be relevant to 2A and 2B.
Keywords: Bouvetøya; Sørishavet; marin biologi; marin zoologi; oseanografi

The water column as an attenuating factor of the UVR effects on bacteria from a coastal Antarctic marine environment - Hernández, Edgardo A; Ferreyra, Gustavo A; Ruberto, Lucas A M; Mac Cormack, Walter P (Polar Research, 2009)
The effect of UVR on the viability of the culturable bacterial community fraction (CBC), and two of their isolated components (Arthrobacter-UVvi and Bizionia-UVps), was studied in the top few metres of the water column at Potter Cove, King George Island, Antarctica. Quartz flasks containing CBC from surface waters were exposed to solar radiation at depths of 0, 1 and 3 m. Similar experiments using UVps and UVvi isolates were performed. In some experiments interferential filters were used to discriminate photosynthetic active radiation (PAR), UV-A and UV-B. CBC from depths of 0, 10 and 30 m were also exposed to surface solar radiation. The deleterious effect of UVR was observed at the surface and at a depth of 1 m, but not at a depth of 3 m. Studies with interferential filters showed low bacterial viability values at depths of 0 and 1 m under both UVR treatments. However, under low radiation doses the effect attributed to UV-B was higher than that caused by UV-A. The surface CBC was more resistant to UVR compared with CBC from a depth of 30 m. The results showed that CBC inhabiting waters above the pycnocline (located at a depth of 5–10 m) are more efficiently adapted to UVR than are those from below the pycnocline. The impact of UVR on the marine bacterioplankton studied was only detected in the first metre of the stratified water column of Potter Cove, which has high levels of suspended particulate matter. These results support the evidence for a significant UVR-attenuating effect in the water column of this coastal Antarctic water.
Keywords: Sørishavet; UV-stråling; bakterier; marin biologi; plankton; statistisk analyse; ultrafiolett stråling; vannsøyle

Vill etter krill : på ekspedisjon med G.O. SARS til Sørishavet - Iversen, Svein A (Red.); Myklevoll, Sigmund (Red.); Mæstad, Kjartan (Red.); Nøttestad, Leif (Red.) (Havforskningsinstituttet, 2009)
Keywords: Sørishavet; ekspedisjoner; euphausiacea; forskning; krill; marin biologi; marine økosystemer; plankton; raudåte

Vill etter krill : på ekspedisjon med G.O. SARS til Sørishavet - Iversen, Svein A; Myklevoll, Sigmund; Mæstad, Kjartan; Nøttestad, Leif; Alvarez, Jaime (Havforskningsinstituttet, 2009)
Keywords: Sørishavet; ekspedisjoner; krill; marin biologi; raudåte; økosystemer

Movements and dive behaviour of two leopard seals (Hydrurga leptonyx) off Queen Maud Land, Antarctica - Nordøy, Erling S; Blix, Arnoldus Schytte (Polar Biology, 2009)
Keywords: Sørishavet; marin biologi; observasjoner; pattedyr; seler; sjøpattedyr

Observations on the relationship between the Antarctic coastal diatoms Thalassiosira antarctica Comber and Porosira glacialis (Grunow) Jørgensen and sea ice concentrations during the late Quaternary - Pike, Jennifer; Crosta, Xavier; Maddison, Eleanor J.; Stickley, Catherine E.; Denis, Delphine; Barbara, Loïc; Renssen, Hans (Marine Micropaleontology, 2009)
The available ecological and palaeoecological information for two sea ice-related marine diatoms (Bacillariophyceae), Thalassiosira antarctica Comber and Porosira glacialis (Grunow) Jørgensen, suggests that these two species have similar sea surface temperature (SST), sea surface salinity (SSS) and sea ice proximity preferences. From phytoplankton observations, both are described as summer or autumn bloom species, commonly found in low SST waters associated with sea ice, although rarely within the ice. Both species form resting spores (RS) as irradiance decreases, SST falls and SSS increases in response to freezing ice in autumn. Recent work analysing late Quaternary seasonally laminated diatom ooze from coastal Antarctic sites has revealed that sub-laminae dominated either by T. antarctica RS, or by P. glacialis RS, are nearly always deposited as the last sediment increment of the year, interpreted as representing autumn flux. In this study, we focus on sites from the East Antarctic margin and show that there is a spatial and temporal separation in whether T. antarctica RS or P. glacialis RS form the autumnal sub-laminae. For instance, in deglacial sediments from the Mertz Ninnis Trough (George V Coast) P. glacialis RS form the sub-laminae whereas in similar age sediments from Iceberg Alley (Mac.Robertson Shelf) T. antarctica RS dominate the autumn sub-lamina. In the Dumont d'Urville Trough (Adélie Land), mid-Holocene (Hypsithermal warm period) autumnal sub-laminae are dominated by T. antarctica RS whereas late Holocene (Neoglacial cool period) sub-laminae are dominated by P. glacialis RS. These observations from late Quaternary seasonally laminated sediments would appear to indicate that P. glacialis prefers slightly cooler ocean–climate conditions than T. antarctica. We test this relationship against two down-core Holocene quantitative diatom abundance records from Dumont d'Urville Trough and Svenner Channel (Princess Elizabeth Land) and compare the results with SST and sea ice concentration results of an Antarctic and Southern Ocean Holocene climate simulation that used a coupled atmosphere–sea ice–vegation model forced with orbital parameters and greenhouse gas concentrations. We find that abundance of P. glacialis RS is favoured by higher winter and spring sea ice concentrations and that a climatically-sensitive threshold exists between the abundance of P. glacialis RS and T. antarctica RS in the sediments. An increase to >0.1 for the ratio of P. glacialis RS:T. antarctica RS indicates a change to increased winter sea ice concentration (to >80% concentration), cooler spring seasons with increased sea ice, slightly warmer autumn seasons with less sea ice and a change from ~7.5months annual sea ice cover at a site to much greater than 7.5months. In the East Antarctic sediment record, an increase in the ratio from <0.1 to above 0.1 occurs at the transition from the warmer Hypsithermal climate into the cooler Neoglacial climate (~4cal kyr) indicating that the ratio between these two diatoms has the potential to be used as a semi-quantitative climate proxy.
Keywords: Sørishavet; Weddellhavet; diatomeer; havis; marin biologi; mikropaleontologi; paleontologi; paleoøkologi; sjøis

Variability and predictability of Antarctic krill swarm structure - Tarling, Geraint A.; Klevjer, Thor; Fielding, Sophie; Watkins, Jon; Atkinson, Angus; Murphy, Eugene; Korb, Rebecca; Whitehouse, Mick; Leaper, Russell (Deep Sea Research Part I: Oceanographic Research Papers, 2009)
Swarming is a fundamental part of the life of Euphausia superba, yet we still know very little about what drives the considerable variability in swarm shape, size and biomass. We examined swarms across the Scotia Sea in January and February 2003 using a Simrad EK60 (38 and 120kHz) echosounder, concurrent with net sampling. The acoustic data were analysed through applying a swarm-identification algorithm and then filtering out all non-krill targets. The area, length, height, depth, packing-concentration and inter-swarm distance of 4525 swarms was derived by this method. Hierarchical clustering revealed 2 principal swarm types, which differed in both their dimensions and packing-concentrations. Type 1 swarms were generally small (<50m long) and were not very tightly packed (<10ind.m−3), whereas type 2 swarms were an order of magnitude larger and had packing concentrations up to 10 times greater. Further sub-divisions of these types identified small and standard swarms within the type 1 group and large and superswarms within the type 2 group. A minor group (swarm type 3) was also found, containing swarms that were isolated (>100km away from the next swarm). The distribution of swarm types over the survey grid was examined with respect to a number of potential explanatory variables describing both the environment and the internal-state of krill (namely maturity, body length, body condition). Most variables were spatially averaged over scales of ∼100km and so mainly had a mesoscale perspective. The exception was the level of light (photosynthetically active radiation (PAR)) for which measurements were specific to each swarm. A binary logistic model was constructed from four variables found to have significant explanatory power (P<0.05): surface fluorescence, PAR, krill maturity and krill body length. Larger (type 2) swarms were more commonly found during nighttime or when it was overcast during the day, when surface fluorescence was low, and when the krill were small and immature. A strong pattern of diel vertical migration was not observed although the larger and denser swarms tended to occur more often at night than during the day. The vast majority of krill were contained within a minor fraction of the total number of swarms. These krill-rich swarms were more common in areas dominated by small and immature krill. We propose that, at the mesoscale level, the structure of swarms switches from being predominantly large and tightly packed to smaller and more diffuse as krill grow and mature. This pattern is further modulated according to feeding conditions and then level of light.
Keywords: Scotiahavet; Sørishavet; ekkolodd; krill; marin biologi; marine økosystemer; plankton

Pleomorphism in the Antarctic flagellate Pyramimonas gelidicola (Prasinophyceae, Chlorophyta) - van den Hoff, John; Ferris, John M (Polar Research, 2009)
Species of the genus Pyramimonas (Prasinophyceae) are a common, widespread, but minor component of the Antarctic marine phytoplankton. They are often associated with the seasonal sea-ice environment. Pyramimonas gelidicola (McFadden, Moestrup & Wetherbee, 1982) was isolated from the water column of a saline Antarctic lake, and observations on the organism’s life history as it grew in unialgal cultures were made. The alga proved to be pleomorphic: capable of producing several morphologically distinct life stages. We recorded motile single-celled quadriflagellates that formed two statistically distinct size classes, a rare uniflagellate cell-type, and aggregations of quadriflagellate cells, multilobed forms and an encystment stage. Multilobed forms and cell aggregations, never before observed in an Antarctic Pyramimonas species, are presumed to be growth medium-induced morphotypes. Multilobed forms contained an equal number of nuclei and lobes, suggesting that they are the product of asexual reproduction. Some of the morphotypes we report here may never be observed under natural field conditions, but the potential for this alga to alternate between morphotypes is clearly demonstrated.
Keywords: Sørishavet; alger; fytoplankton; marin biologi

Sedimentological, geochemical and palaeontological evidence for a neoglacial cold event during the late Holocene in the continental shelf of the northern South Shetland Islands, West Antarctica - Yoo, Kyu-Cheul; Yoon, Ho Il; Kim, Jin-Kyung; Khim, Boo-Keun (Polar Research, 2009)
Two sediment cores obtained from the continental shelf of the northern South Shetland Islands, West Antarctica, consist of: an upper unit of silty mud, bioturbated by a sluggish current, and a lower unit of well-sorted, laminated silty mud, attributed to an intensified Polar Slope Current. Geochemical and accelerator mass spectrometry 14C analyses yielded evidence for a late Holocene increase in sea-ice extent and a decrease in phytoplankton productivity, inferred from a reduction in the total organic carbon content and higher C : N ratios, at approximately 330 years B.P., corresponding to the Little Ice Age. Prior to this, the shelf experienced warmer marine conditions, with greater phytoplankton productivity, inferred from a higher organic carbon content and C : N ratios in the lower unit. The reduced abundance of Weddell Sea ice-edge bloom species (Chaetoceros resting spores, Fragilariopsis curta and Fragilariopsis cylindrus) and stratified cold-water species (Rhizosolenia antennata) in the upper unit was largely caused by the colder climate. During the cold period, the glacial restriction between the Weddell Sea and the shelf of the northern South Shetland Islands apparently hindered the influx of ice-edge bloom species from the Weddell Sea into the core site. The relative increases in the abundance of Actinocyclus actinochilus and Navicula glaciei, indigenous to the coastal zone of the South Shetland Islands, probably reflects a reduction in the dilution of native species, resulting from the diminished influx of the ice-edge species from the Weddell Sea. We also document the recent reduction of sea-ice cover in the study area in response to recent warming along the Antarctic Peninsula.
Keywords: Antarktis; Den lille istid; Vestantarktis; Weddellhavet; diatomeer; fytoplankton; geokjemi; havis; klimaendringer; klimatologi; kontinentalsokkel; marin biologi; mikropaleontologi; oseanografi; sedimenter; sedimentologi; sjøis

Southern Ocean frontal structure and sea-ice formation rates revealed by elephant seals - Charrassin, J.-B.; Hindell, M.; Rintoul, S. R.; Roquet, F.; Sokolov, S.; Biuw, M.; Costa, D.; Boehme, L.; Lovell, P.; Coleman, R.; Timmermann, R.; Meijers, A.; et al. (Proceedings of the National Academy of Sciences, 2008)
Polar regions are particularly sensitive to climate change, with the potential for significant feedbacks between ocean circulation, sea ice, and the ocean carbon cycle. However, the difficulty in obtaining in situ data means that our ability to detect and interpret change is very limited, especially in the Southern Ocean, where the ocean beneath the sea ice remains almost entirely unobserved and the rate of sea-ice formation is poorly known. Here, we show that southern elephant seals (Mirounga leonina) equipped with oceanographic sensors can measure ocean structure and water mass changes in regions and seasons rarely observed with traditional oceanographic platforms. In particular, seals provided a 30-fold increase in hydrographic profiles from the sea-ice zone, allowing the major fronts to be mapped south of 60°S and sea-ice formation rates to be inferred from changes in upper ocean salinity. Sea-ice production rates peaked in early winter (April?May) during the rapid northward expansion of the pack ice and declined by a factor of 2 to 3 between May and August, in agreement with a three-dimensional coupled ocean?sea-ice model. By measuring the high-latitude ocean during winter, elephant seals fill a ?blind spot? in our sampling coverage, enabling the establishment of a truly global ocean-observing system.
Keywords: Sørishavet; havis; hydrografi; klimaendringer; marin biologi; oseanografi; polarområdene; sjøelefanter; sjøis; sjøpattedyr

Regeneration of Fe(II) during EIFeX and SOFeX - Croot, Peter L.; Bluhm, Kathrin; Schlosser, Christian; Streu, Peter; Breitbarth, Eike; Frew, Russell D.; Ardelan, Murat van (Geophysical Research Letters, 2008)
Investigations into Fe(II) cycling during two Southern Ocean mesoscale iron enrichment experiments, SOFeX and EIFeX, clearly show the importance of Fe(II) to iron speciation during these experiments. In both cases the added Fe(II) persisted significantly longer than its expected oxidation time indicating a significant Fe reduction process at work. During EIFeX diel studies showed a strong photochemically induced cycle in Fe(II) production in sunlit surface waters. Our results suggest that the photochemical cycling of iron may also be important in unfertilized waters of the Southern Ocean.
Keywords: Sørishavet; biogeokjemi; fytoplankton; marin biologi; polarområdene

Decline in energy storage in the Antarctic minke whale (Balaenoptera bonaerensis) in the Southern Ocean - Konishi, Kenji; Tamura, Tsutomu; Zenitani, Ryoko; Bando, Takeharu; Kato, Hidehiro; Walløe, Lars (Polar Biology, 2008)
The annual trend in energy storage in the Antarctic minke whale was examined using catch data from all 18 survey years in the Japanese Whale Research Program (JARPA). Regression analyses clearly showed that blubber thickness, girth and fat weight have been decreasing for nearly 2 decades. The decrease per year is estimated at approximately 0.02 cm for mid-lateral blubber thickness and 17 kg for fat weight, corresponding to 9% for both measurements over the 18-year period. Furthermore, "date", "extent of diatom adhesion", "sex", "body length", "fetus length", "latitude", "age" and "longitude" were all identified as partially independent predictors of blubber thickness. The direct interpretation of this substantial decline in energy storage in terms of food availability is difficult, since no long-term krill abundance series is available. However, an increase in the abundance of krill feeders other than minke whales and a resulting decrease in the krill population must be considered as a likely explanation.
Keywords: Sørishavet; hvaler; krill; marin biologi; plankton; vågehvaler

Comparison of contemporary and fossil diatom assemblages from the western Antarctic Peninsula shelf - Pike, Jennifer; Allen, Claire S.; Leventer, Amy; Stickley, Catherine E.; Pudsey, Carol J. (Marine Micropaleontology, 2008)
During the past ten years, the Antarctic Peninsula has been identified as the most rapidly warming region of the Southern Hemisphere and it is important to place this warming in the context of the natural climate and oceanographic variability of the recent geological past. Many biological proxies, such as marine diatom assemblages, have been used to determine Southern Ocean palaeoceanographic conditions during the Late Quaternary, however, few investigations have attempted to link observations of modern floras with the fossil record. In this study we examine a suite of modern austral spring (December 2003) and summer (February 2002) surface water samples from along the western Antarctic Peninsula (WAP) continental shelf and compare these to core-top, surface sediment samples. Using detrended correspondence analysis (DCA) and principal component analysis (PCA) of diatom abundance data we investigate the relationship of contemporary diatom floras with the fossil record. This multivariate analysis reveals that our modern assemblages can be divided into three groups: summer southern WAP sites, summer northern WAP sites, and spring WAP sites. Sea surface temperature (SST) is an important environmental variable for explaining seasonal differences in diatom assemblages between spring and summer, but sea surface salinity (SSS) is more important for understanding temporally-equivalent regional variations in assemblage. Our summer diatom samples are more reminiscent of early season assemblages, reflecting the unusually late sea ice retreat from the region that year. When the modern assemblages are compared to the fossil record, it is clear that most of the important diatoms from the summer assemblage are not preserved into the sediments, and that the fossil record more closely reflects spring assemblages. This observation is important for any future attempts to quantitatively reconstruct palaeoceanographic conditions along the WAP during the Late Quaternary and highlights the need for many more such studies in order to address longer timescales, such as interannual variability, in the context of the fossil record.
Keywords: Sørishavet; Vestantarktis; diatomeer; marin biologi; marin geologi; mikropaleontologi; paleoseanografi

Rødt gull i Sørishavet - Stephansen, Susanne Moen (Polaråret: et magasin om det internasjonale polaråret 2007-2008, 2008)
En rekelignende skapning i Sørishavet er Kjell Inge Røkkes nye yndling. Den kan nemlig brukes i alt fra slankemidler til fiskefôr. Men vet vi nok om krill til å slippe trålerne løs? Forskningsskipet G.O. Sars har vært på tokt for å finne u mer.
Keywords: Sørishavet; krill; marin biologi

Blocking primers to enhance PCR amplification of rare sequences in mixed samples – a case study on prey DNA in Antarctic krill stomachs - Vestheim, Hege; Jarman, Simon N. (Frontiers in Zoology, 2008)
Identification of DNA sequence diversity is a powerful means for assessing the species present in environmental samples. The most common molecular strategies for estimating taxonomic composition depend upon PCR with universal primers that amplify an orthologous DNA region from a range of species. The diversity of sequences within a sample that can be detected by universal primers is often compromised by high concentrations of some DNA templates. If the DNA within the sample contains a small number of sequences in relatively high concentrations, then less concentrated sequences are often not amplified because the PCR favours the dominant DNA types. This is a particular problem in molecular diet studies, where predator DNA is often present in great excess of food-derived DNA.
Keywords: Scotiahavet; Sørishavet; genetikk; genetisk analyse; krill; marin biologi; plankton; taksonomi

Growth rate and its variability in erect Antarctic bryozoans - Barnes, David K. A.; Webb, Karen E.; Linse, Katrin (Polar Biology, 2007)
Climate is altering rapidly in parts of the Arctic and Antarctic but we know little about how marine organisms are responding to, or might respond to such changes. Knowledge of within-taxon variability is the vital context (currently missing) to interpretation of environmental signals. We investigated growth in six species and three genera of erect Antarctic bryozoans, an ideal model taxon to investigate such response. Cellarinella margueritae, C. nodulata, C. rogickae, C. watersi, Melicerita obliqua and Stomhypselosaria watersi, extended 3.4, 5.2, 4.6, 4.1, 4.9 and 4.5 mm year(-1) and synthesised 24, 55, 45, 176, 34 and 46 mg CaCO3 year(-1), respectively. The maximum ages of these species ranged from 11 to 15 years except M. obliqua, which reached 32 years. This is the first investigation of growth rates of closely related Antarctic invertebrate species and reports the slowest growth rates of bryozoans known from anywhere to date. Our data coupled with that from literature shows that Antarctic bryozoan growth varies << 10(1) between species, 10(1) between genera, 10(2) between morphologies and is similar to 10(1) slower than in tropical or temperate regions. However, within encrusting types the slowest growing species grow at similar rates from poles to tropics. Age was a strong confounding factor across our Antarctic study species but age-standardised data showed a possible decline in annual growth from 1992 to 2003. We identify several factors increasing this environmental signal strength, including (1) the importance of generic (though not necessarily species) identification and (2) use of dry-mass or ash-free dry-mass as the measures of growth.
Keywords: Sørishavet; bryozoa; klimaendringer; marin biologi; mosdyr

Variations in behavior and condition of a Southern Ocean top predator in relation to in situ oceanographic conditions - Biuw, Martin; Boehme, L.; Guinet, C.; Hindell, M.; Costa, D.; Charrassin, J.-B.; Roquet, F.; Bailleul, F.; Meredith, M.; Thorpe, S.; Tremblay, Y.; McDonald, B.; et al. (Proceedings of the National Academy of Sciences, 2007)
Responses by marine top predators to environmental variability have previously been almost impossible to observe directly. By using animal-mounted instruments simultaneously recording movements, diving behavior, and in situ oceanographic properties, we studied the behavioral and physiological responses of southern elephant seals to spatial environmental variability throughout their circumpolar range. Improved body condition of seals in the Atlantic sector was associated with Circumpolar Deep Water upwelling regions within the Antarctic Circumpolar Current, whereas High-Salinity Shelf Waters or temperature/salinity gradients under winter pack ice were important in the Indian and Pacific sectors. Energetic consequences of these variations could help explain recently observed population trends, showing the usefulness of this approach in examining the sensitivity of top predators to global and regional-scale climate variability.
Keywords: Sørishavet; marin biologi; oseanografi; sjøelefanter

Ross seal (Ommatophoca rossii) annual distribution, diving behaviour, breeding and moulting, off Queen Maud Land, Antarctica - Blix, Arnoldus Schytte; Nordøy, Erling S. (Polar Biology, 2007)
Six out of ten adult Ross seals that were tagged with Argos satellite-linked dive recorders off Queen Maud Land, just after the moult in February, provided data on location and diving activity throughout a year. Shortly after tagging, the animals headed 2,000 km north and stayed pelagic in the area south of the Antarctic Polar Front, until October when they went south into the pack-ice. Throughout the year they made about 100 dives a day, most to a depth of 100–300 m, the deepest dive on record being 792 m, while some dives were very shallow during their stay in the pack-ice. Most dives, outside the breeding and moulting period, lasted for 5–15 min throughout the year. This diving behaviour is consistent with feeding on mid-water fish, like Pleurogramma antarcticum, squid, and to some extent krill (Euphausia superba), when in the pack-ice, and myctophid fish and several species of squid, when in the open ocean. The nursing period was 13 days in mid-November, and moulting occurs in late January–early February, which is the period when sightings surveys for this species should be done.
Keywords: Sørishavet; marin biologi; pinnipedier; satellittsendere; seler; telemetri; zoologi

Diversity and species distribution of polychaetes, isopods and bivalves in the Atlantic sector of the deep Southern Ocean - Ellingsen, Kari E.; Brandt, Angelika; Ebbe, Brigitte; Linse, Katrin (Polar Biology, 2007)
We examined deep-sea benthic data on polychaetes, isopods and bivalves from the Atlantic sector of the Southern Ocean. Samples were taken during the expeditions EASIZ II (1998), ANDEEP I and II (2002) (depth: 742-6,348 m). The range between sites varies from 3 to 1,900 km. Polychaetes (175 species in total) and isopods (383 species) had a high proportion of species restricted to one or two sites (72 and 70%, respectively). Bivalves (46 species) had a higher proportion of species represented at more sites. Beta diversity (Whittaker and Jaccard) was higher for polychaetes and isopods than for bivalves. The impact of depth on species richness was not consistent among groups; polychaetes showed a negative relationship to depth, isopods displayed highest richness in the middle depth range (2,000-4,000 m), whereas bivalves showed no clear relationship to depth. Species richness was not related to latitude (58-74 degrees S) or longitude (22-60 degrees W) for any group.
Keywords: Sørishavet; biodiversitet; flerbørstemarker; isopoder; marin biologi; muslinger; skjell; tanglus

Det første forskningstoktet til Antarktis - Tofte, Kari Østervold (Polaråret: et magasin om det internasjonale polaråret 2007-2008, 2007)
Keywords: Sørishavet; forskning; marin biologi

Quantitative analysis of soft-bottom molluscs in the Bellingshausen Sea and around Peter I Island - Troncoso, Jesús S; Aldea, Cristian; Arnaud, Patrick; Ramos, Ana; García, Francisco (Polar Research, 2007)
Macrobenthic soft-bottom molluscs were sampled in 30 stations located in the Bellingshausen Sea at depths ranging from 90 to 3304 m. The samples were collected using a quantitative grab box-corer during the cruises BENTART 03, from 24 January to 3 March 2003, and BENTART 06, from 2 January to 16 February 2006. Molluscs represent 1074 specimens belonging to 62 species of Polyplacophora, Gastropoda, Bivalvia and Scaphopoda. The bivalve Cyamiocardium denticulatum was the most abundant species (448 specimens). The abundance per station varied between 1 and 446 specimens. The Shannon–Wiener diversity index ranged between one specimen and 2.36, the Pielou evenness index ranged between 0.00 and 1 and species richness ranged from 1 to 14 species. Diversity showed great variations at different stations. After multivariate analysis (cluster analysis and nonmetrical multidimensional scaling) based on Bray–Curtis similarities, we were able to separate two principal clusters. The first cluster groups together species from shallower bottoms near Peter I Island and the Antarctic Peninsula, and the second cluster groups together species from deeper bottoms in the Bellingshausen Sea. The combination of environmental variables with the highest correlations with faunistic data was that of depth and coarse sand at the surface.
Keywords: Peter I. Øy; Sørishavet; bløtdyr; marin biologi; marine økosystemer; mollusker; oseanografi

Crustacea in Arctic and Antarctic Sea Ice: Distribution, Diet and Life History Strategies - Arndt, Carolin E.; Swadling, Kerrie M. (Advances in Marine Biology, 2006)
This review concerns crustaceans that associate with sea ice. Particular emphasis is placed on comparing and contrasting the Arctic and Antarctic sea ice habitats, and the subsequent influence of these environments on the life history strategies of the crustacean fauna. Sea ice is the dominant feature of both polar marine ecosystems, playing a central role in physical processes and providing an essential habitat for organisms ranging in size from viruses to whales. Similarities between the Arctic and Antarctic marine ecosystems include variable cover of sea ice over an annual cycle, a light regimen that can extend from months of total darkness to months of continuous light and a pronounced seasonality in primary production. Although there are many similarities, there are also major differences between the two regions: The Antarctic experiences greater seasonal change in its sea ice extent, much of the ice is over very deep water and more than 80% breaks out each year. In contrast, Arctic sea ice often covers comparatively shallow water, doubles in its extent on an annual cycle and the ice may persist for several decades. Crustaceans, particularly copepods and amphipods, are abundant in the sea ice zone at both poles, either living within the brine channel system of the ice‐crystal matrix or inhabiting the ice–water interface. Many species associate with ice for only a part of their life cycle, while others appear entirely dependent upon it for reproduction and development. Although similarities exist between the two faunas, many differences are emerging. Most notable are the much higher abundance and biomass of Antarctic copepods, the dominance of the Antarctic sea ice copepod fauna by calanoids, the high euphausiid biomass in Southern Ocean waters and the lack of any species that appear fully dependent on the ice. In the Arctic, the ice‐associated fauna is dominated by amphipods. Calanoid copepods are not tightly associated with the ice, while harpacticoids and cyclopoids are abundant. Euphausiids are nearly absent from the high Arctic. Life history strategies are variable, although reproductive cycles and life spans are generally longer than those for temperate congeners. Species at both poles tend to be opportunistic feeders and periods of diapause or other reductions in metabolic expenditure are not uncommon.
Keywords: Sørishavet; copepoder; crustacea; havis; krill; marin biologi; plankton; polarområdene; sjøis

The biodiversity of the deep Southern Ocean benthos - Brandt, A; De Broyer, C; De Mesel, I; Ellingsen, K.E; Gooday, A.J; Hilbig, B; Linse, K; Thomson, M.R.A; Tyler, P.A (Philosophical Transactions of the Royal Society B: Biological Sciences, 2006)
Our knowledge of the biodiversity of the Southern Ocean (SO) deep benthos is scarce. In this review, we describe the general biodiversity patterns of meio-, macro- and megafaunal taxa, based on historical and recent expeditions, and against the background of the geological events and phylogenetic relationships that have influenced the biodiversity and evolution of the investigated taxa. The relationship of the fauna to environmental parameters, such as water depth, sediment type, food availability and carbonate solubility, as well as species interrelationships, probably have shaped present-day biodiversity patterns as much as evolution. However, different taxa exhibit different large-scale biodiversity and biogeographic patterns. Moreover, there is rarely any clear relationship of biodiversity pattern with depth, latitude or environmental parameters, such as sediment composition or grain size. Similarities and differences between the SO biodiversity and biodiversity of global oceans are outlined. The high percentage (often more than 90%) of new species in almost all taxa, as well as the high degree of endemism of many groups, may reflect undersampling of the area, and it is likely to decrease as more information is gathered about SO deep-sea biodiversity by future expeditions. Indeed, among certain taxa such as the Foraminifera, close links at the species level are already apparent between deep Weddell Sea faunas and those from similar depths in the North Atlantic and Arctic. With regard to the vertical zonation from the shelf edge into deep water, biodiversity patterns among some taxa in the SO might differ from those in other deep-sea areas, due to the deep Antarctic shelf and the evolution of eurybathy in many species, as well as to deep-water production that can fuel the SO deep sea with freshly produced organic matter derived not only from phytoplankton, but also from ice algae.
Keywords: Sørishavet; bentos; biodiversitet; biogeografi; marin biologi

Entanglement of Antarctic fur seals at Bouvetøya, Southern Ocean - Greg Hofmeyr, G J; Bester, Marthán N; Kirkman, Steve P; Lydersen, Christian; Kovacs, Kit M (Marine Pollution Bulletin, 2006)
Keywords: Bouvetøya; forurensning; marin biologi; pelsseler; pinnipedier

Entanglement of Antarctic fur seals at Bouvetøya, Southern Ocean - Greg Hofmeyr, G.J.; Bester, Marthán N.; Kirkman, Steve P.; Lydersen, Christian; Kovacs, Kit M. (Marine Pollution Bulletin, 2006)
Entanglements of Antarctic fur seals Arctocephalus gazella were recorded during four summers from 1996 to 2002 at the subantarctic island, Bouvetøya. Rates of entanglement varied between 0.024% and 0.059%. These rates are low for a pinniped population and might be because of the geographic isolation of the haulout site. An apparent decrease in the levels of entanglement over the course of the study was likely due, at least in part, to the removal of entanglements by observers. At least two-thirds of entangling materials were generated by fishery sources. Since there is no known local source of anthropogenic marine pollution, seals become entangled either in waters distant from the island, or when materials drift into local waters. Significantly more subadults were found entangled than expected from the postulated population age class distribution.
Keywords: Bouvetøya; Sørishavet; marin biologi; marin forurensning; pelsseler; pinnipedier

Cetacean feeding, growth and energetics in relation to the marine ecosystem - implications for management? - Lockyer, Christina (Whaling and History II : new perspectives, 2006)
Keywords: Sørishavet; hvaler; hvalfangst; marin biologi; marine økosystemer

Comparison of the microalgal community within fast ice at two sites along the Ross Sea coast, Antarctica - Ryan, K.G.; Hegseth, E.N.; Martin, A.; Davy, S.K.; O'Toole, R.; Ralph, P.J.; McMinn, A.; Thorn, C.J. (Antarctic Science, 2006)
Diverse microbial communities survive within the sea ice matrix and are integral to the energy base of the Southern Ocean. Here we describe initial findings of a four season survey (between 1999–2004) of community structure and biomass of microalgae within the sea ice and in the underlying water column at Cape Evans and Cape Hallett, in the Ross Sea, Antarctica as part of the Latitudinal Gradient Project. At Cape Evans, bottom-ice chlorophyll a levels ranged from 4.4 to 173 mg Chl a m−2. Dominant species were Nitzschia stellata, N. lecointei, and Entomoneis kjellmanii, while the proportion of Berkeleya adeliensis increased steadily during spring. Despite being obtained later in the season, the Cape Hallett data show considerably lower standing stocks of chlorophyll ranging from 0.11 to 36.8 mg Chl a m−2. This difference was attributed to a strong current, which may have ablated much of the bottom ice biomass and provided biomass to the water below. This loss of algae from the bottom of the ice may explain why the ice community contributed only 2% of the standing stock in the total water column. Dominant species at Cape Hallett were Nitzschia stellata, Fragilariopsis curta and Cylindrotheca closterium. The low biomass at Cape Hallett and the prevalence of smaller-celled diatoms in the bottom ice community indicate that the ice here is more typical of pack ice than fast ice. Further data will allow us to quantify and model the extent to which ice-driven dynamics control the structure and function of the sea ice ecosystem and to assess its resilience to changing sea ice conditions.
Keywords: Rosshavet; Sørishavet; alger; biomasse; fytoplankton; marin biologi

Bipolar patterns of intraspecific competition in bryozoans - Barnes, David K A; Kuklinski, Piotr (Marine Ecology Progress Series, 2005)
Polar shores probably represent the most dynamic and extremely disturbed environments on the globe. Nevertheless intense battles amongst sessile organisms for space are commonplace on hard substrata, mainly between fast-growing pioneer species. In this study we examined spatial interactions in encrusting species at 3 sites within each of 2 high Arctic localities, Horsundfjord (77°N) and Kongsfjord (79°N) in Spitsbergen, and 2 Antarctic localities, Signy Island (60°S) and Adelaide Island (68°S). In both polar regions 1 to 11% of encrusting fauna were involved in intraspecific interactions. Intraspecific competition was common; it usually involved just 1 or 2 pioneer species, mainly ended in tied outcomes, and most variability was at a local scale. The proportion of intraspecific encounters varied considerably at local (km) scales (19 to 99% intraspecific at different sites), reflecting an extremely patchy environment due to ice scour. Most intraspecific encounters resulted in ties (stand-offs) and again most variability was at a local scale. Many intraspecific encounters were constructive, forming large (>1 m3) foliaceous colonies (termed bioconstructions) whose 3D structures can harbour rich biotas. In other colonies intraspecific competition caused crowding and accelerated ovicell production (reproductive activity). Homosyndrome (fusion) was not observed in the Arctic and was rare in the Antarctic, where its frequency differed significantly between competitor identities. We found that the likelihood of meeting conspecifics versus other species and of tied outcomes in encounters was related to the performance of species in interspecific competition: ties were most common, and homosyndrome only occurred in poor competitors. In the context of rapid Arctic and west Antarctic warming and ice-loading of nearshore waters, we predict strongly changing patterns of intraspecific competition. Indeed we suggest that decreased patchiness of intra- versus interspecific competition and decreased levels of intraspecific competition should be strong indicators of increases in surface water ice-loading from ice-sheet collapses. KEYWORDS: Sublittoral · Benthos · Bioconstruction · Climate change · Homosyndrome
Keywords: Sørishavet; bentiske organismer; bryozoa; klimaendringer; marin biologi; miljøendringer; oseanografi; polarområdene

Southern Ocean deep-sea isopod species richness (Crustacea, Malacostraca): influences of depth, latitude and longitude - Brandt, Angelika; Ellingsen, Kari E.; Brix, Saskia; Brökeland, Wiebke; Malyutina, Marina (Polar Biology, 2005)
We examined deep-sea epibenthic sledge isopod data from the Atlantic sector of the Southern Ocean (SO) (depth range=742–5,191 m). Samples were taken during the expeditions EASIZ II (ANT XV-3) in 1998 and ANDEEP I and II (ANT XIX3/4) in 2002. A total of 471 isopod species were recorded from 28 sites. The species richness of the epibenthic sledge samples was highly variable (6–82 species). Species richness was highest at site 131-3 in 3,053 m depth in the north-eastern Weddell Sea. The highest numbers of species were sampled in the middle depth range and lower species richness was found in the shallower and deeper parts of the study area. Depth is suggested to explain isopod species richness better than both latitude and longitude. Between 58°S and 65°S, the number of species ranged from 9 to 82 (mean=35.9). Further south in the Weddell Sea, between 73°S and 74°S, species richness was lower and the number of species ranged from 6 to 35 (mean=19.2). With regard to longitude, the highest species richness (up to 82 species) was found between 50°W and 60°W in the area of the South Shetland Islands and around the Antarctic Peninsula, while numbers did not exceed 50 species in the eastern Weddell Sea. The haul length, ranging from 807 to 6,464 m, was positively correlated with depth; however, there was no linear relationship between haul length and species richness. We therefore suggest that depth was the most important factor explaining isopod species richness. However, only 28 sites were visited and the statistical power is thus limited. Sampling in the deep sea is expensive and time consuming and as yet this is the best isopod data set available from the Atlantic sector of the SO. Future expeditions are therefore important to better explain the current patterns of benthic diversity in Antarctica.
Keywords: Sør-Shetlandsøyene; Sørishavet; Weddellhavet; biodiversitet; isopoder; marin biologi

Polar bivalves are characterized by high antioxidant defences - Camus, Lionel; Gulliksen, Bjørn; Depledge, Michael H; Jones, Malcolm B (Polar Research, 2005)
Inevitably, aerobic life leads to the formation of deleterious reactive oxygen species (ROS) which participate in biomolecule oxidation, hence augmenting biomolecule turnover. Organisms have adapted to counteract the noxious effects of ROS by developing a battery of antioxidant defences (AOX) which comprise enzymes and low-molecular weight scavengers. Past studies have reported elevated AOX levels in polar pectinid bivalves compared with temperate congeners. This fi nding is controversial as mitochondrial ROS generation is low in polar versus temperate species, and, to date, there is no generally accepted explanation of the causes of increased basal AOX levels in polar waters. We suggest that the low food availability in those ecosystems may result in polar marine ectotherms diverting some energy into the maintenance of high AOX. We tested this hypothesis by comparing the total oxyradical scavenging capacity (peroxyl, hydroxyl and peroxynitrite) of three clam species: Laternula elliptica (Antarctic), Mya truncata (Arctic) and Mya arenaria (temperate). The data confi rmed that polar bivalves are characterized by higher AOX. Herein, we propose that high AOX is required in environments characterized by low food availability as AOX effi ciently protects biomolecules, notably the RNA expressed at high levels by cold-water ectotherms. Also, high AOX may explain the relatively long lifespan of most polar ectotherms.
Keywords: Sørishavet; marin biologi; muslinger; polarområdene

Population changes of Antarctic fur seals at Nyrøysa, Bouvetøya - Hofmeyr, Greg; Krafft, Bjørn; Kirkman, Stephen; Bester, Marthán; Lydersen, Christian; Kovacs, Kit (Polar Biology, 2005)
Antarctic fur seal Arctocephalus gazella pup production at Nyrøysa, Bouvetøya was estimated to be approximately 15,000 per annum during each of four summers from 1996 to 2002, indicating a total population of about 66,000. While the Bouvetøya population is the second largest for this species, pup production at this site still accounts for only 2.4% of the global total. This population experienced a mean annual rate of increase of 30.6% for the period 1989–1996, perhaps due, in part, to significant immigration, but has been stable since 1996. Historical accounts of significant numbers of animals being present towards the end of the period of sealing (C.1800–1930), indicate that the geographic isolation and inaccessibility of this site may have resulted in the Bouvetøya population being one of three populations that survived a series of periods of extreme exploitation of this species.
Keywords: Bouvetøya; marin biologi; pelsseler; pinnipedier; seler; zoologi

Telonema antarcticum sp. nov., a common marine phagotrophic flagellate - Klaveness, Dag; Shalchian-Tabrizi, Kamran; Thomsen, Helge Abildhauge; Eikrem, Wenche; Jakobsen, Kjetill S. (International Journal of Systematic and Evolutionary Microbiology, 2005)
Telonema is a widely distributed group of phagotrophic flagellates with two known members. In this study, the structural identity and molecular phylogeny of Telonema antarcticum was investigated and a valid description is proposed. Molecular phylogeny was studied using small-subunit rRNA (SSU rRNA) gene sequences. The pear-shaped cell had two subequal flagella that emerged laterally on the truncated antapical tail. One flagellum had tripartite hairs. The cell was naked, but had subsurface vesicles containing angular paracrystalline bodies of an unknown nature. A unique complex cytoskeletal structure, the subcortical lamina, was found to be an important functional and taxonomic feature of the genus. Telonema has an antero-ventral depression where food particles are ingested and then transferred to a conspicuous anterior food vacuole. The molecular phylogeny inferred from the SSU rRNA gene sequence suggested that Telonema represents an isolated and deep branch among the tubulocristate protists.
Keywords: Sørishavet; Weddellhavet; fylogenetikk; marin biologi; mikrobiologi

Isolation and partial characterization of a parapoxvirus isolated from a skin lesion of a Weddell seal - Tryland, M.; Klein, J.; Nordøy, E.S.; Blix, A.S. (Virus Research, 2005)
A solitary skin lesion was found on the neck of a Weddell seal (Leptonychotes weddellii), chemically immobilized in Queen Maud Land (70°09′S, 05°22′E) Antarctica 2001. The lesion was elevated and 3cm in diameter, consisting of partly fresh and partly necrotic tissue, and proliferative papilloma-like structures were seen. Electron microscopy on a biopsy from the lesion revealed typical parapoxvirus particles. Polymerase chain reaction (PCR; B2L gene) generated amplicons of approximately 594 base pairs, comparable to Orf-virus, the prototype parapoxvirus. A comparison of these B2L PCR amplicon DNA sequences with corresponding sequences from other parapoxviruses, showed that the Weddell seal virus resembled isolates from grey seal (Halichoerus grypus) and harbour seal (Phoca vitulina) more than parapoxvirus from red deer (Cervus elaphus), sheep, cattle and Japanese serows (Capricornis crispus). It is thus concluded that the Weddell seal parapoxvirus belong to the tentative seal parapoxvirus species. Since parapox and orthopoxviruses may cause similar clinical diseases, we suggest that the term sealpox should be restricted to the clinical disease, whereas seal parapoxvirus should be used when caused by a parapoxvirus, rather than the general term “sealpox virus”. This is the first verified case of parapoxvirus infection in a Weddell seal, and also the first report of any such infections in the Antarctic.
Keywords: Dronning Maud Land; Weddellhavet; fylogenetikk; marin biologi; mikrobiologi; pinnipedier; seler; virologi

Interannual controls on Weddell Sea surface water fCO2 during the autumn–winter transition phase - Bellerby, Richard G.J.; Hoppema, Mario; Fahrbach, Eberhard; de Baar, Hein J.W.; Stoll, Michel H.C. (Deep Sea Research Part I: Oceanographic Research Papers, 2004)
The fugacity of carbon dioxide (fCO2) of the surface waters of the Weddell Sea along the prime meridian has been described for the austral autumn in 1996 and 1998. For individual years, fCO2 has a strong linear relationship with sea surface temperature, although the relationships cannot be reconciled to provide an interannually consistent algorithm for remotely sensed assessment of fCO2. However, from the assumption that Weddell Sea surface water has a single end member (upwelled Warm Deep Water) we have determined the relative contributions of heating, ice-melt, and biological activity on fCO2. A breakdown of the controls shows that the measured annual fCO2 distributions can be recreated for both transects by adjusting solely for thermodynamic forcing, and model adjustments for salinity are small except in regions of significant upwelling during 1998. The incorporation of nitrate utilisation into the model results in a general and significant underestimation of fCO2. This runs contrary to the earlier findings of Sabine and Key (Mar. Chem. 60 (1998) 95) in the Southern Ocean although it is consistent with models in the area (Louanchi et al., Deep-Sea Res. I 48 (2001) 1581). A major caveat to these findings is the significant departure of the thermodynamic model and a tightening of the nitrate-adjusted model in 1998 in areas with deeper mixing in the southern Weddell Sea. We propose that there are two reasons for the discrepancies in our model: the source waters are not as homogenous as the model assumes; and there are geographical and seasonal variations of CO2 exchange with the atmosphere and the input of inorganic carbon and nitrate from below the mixed layer resulting in imbalances in the mixed layer concentration ratios.
Keywords: Sørishavet; Weddellhavet; karbon syklus; karbondioksid; marin biologi; marin kjemi; oseanografi

Diesel oil and PCB-degrading psychrotrophic bacteria isolated from Antarctic seawaters (Terra Nova Bay, Ross Sea) - De Domenico, Maria; Lo Giudice, Angelina; Michaud, Luigi; Saitta, Marcello; Bruni, Vivia (Polar Research, 2004)
Fifty-seven Antarctic marine bacteria were examined for their ability to degrade commercial diesel oil as the sole organic substrate at both 4 °C and 20 °C. Based on the preliminary screening, two isolates (B11 and B15) with high capacity to degrade diesel oil were selected and their biodegradation effi ciency was quantifi ed by gas chromatographic analysis. As expected for psychrotrophs, diesel oil biodegradation was slower at 4 °C than at 20 °C. The two strains also mineralized the C28 n-paraffi n octacosane at 20 °C and polychlorinated biphenyls (PCBs) at 4 °C and 20 °C.
Keywords: Rosshavet; Sørishavet; bakterier; biologisk nedbrytning; kjemi; marin biologi; marin økologi

Effect of solar radiation and the subsequent dark periods on two newly isolated and characterized Antarctic marine bacteria - Hernández, Edgardo A; Ferreyra, Gustavo A; Mac Cormack, Walter P (Polar Research, 2004)
Two strains of psychrotolerant Antarctic marine bacteria were isolated and characterized using biochemical and molecular techniques. Sequencing of 16S rRNA gene showed that UVvi strain belongs to the genus Arthrobacter whereas UVps strain is related to the Flexibacter-Cytophaga-Bacteroides (FCB) group. Response of the strains to solar radiation was studied during the summer of 1999 in Potter Cove, near Jubany station (South Shetland Island, Antarctica). The effect of photosynthetically available radiation (PAR, 400-700 nm), ultraviolet-A (UV-A, 320-400 nm) and ultraviolet-B radiation (UV-B, 280-320 nm) on cell viability was studied using mixed cultures in quartz bottles covered with interferential filters and exposed to solar radiation. In all experiments, four treatments were used: dark (with light screened out), PAR (with UV radiation screened out), PAR+UV-A (UV-B screened out) and PAR+UV-A+UV-B. Under the assayed conditions, PAR+UV-A and PAR+UV-A+UV-B radiation showed similar negative effects on the viability of the studied strains. However, at the end of the exposure time, mortality values in PAR+UV-A+UV-B treatments were higher than those observed under PAR+UV-A treatments. In both PAR+UV-A and PAR+UV-A+UV-B treatments we observed high levels of hydrogen peroxide compared with the dark control. The Arthrobacter UVvi strain showed significant recovery in dark conditions after exposure to the PAR+UV-A but not after the PAR+UV-A+UV-B treatment. This strain proved to be more resistant to UV radiation than the FCB group-related UVps strain. The results showed that UV radiation has a deleterious effect on these Antarctic marine bacteria and also revealed that the analysed components of the Antarctic bacterioplankton may have different responses when they are exposed to the same irradiance conditions.
Keywords: Sørishavet; UV-stråling; bakterier; biokjemi; marin biologi; ozonlaget; plankton; ultrafiolett stråling

Iron enrichment and photoreduction of iron under UV and PAR in the presence of hydroxycarboxylic acid: implications for phytoplankton growth in the Southern Ocean - Öztürk, Murat; Croot, Peter L.; Bertilsson, Stefan; Abrahamsson, Katarina; Karlson, Bengt; David, Roland; Fransson, Agneta; Sakshaug, Egil (The SWEDARP 1997/98 Expedition, 2004)
Iron(III) photoreduction and the responses of phytoplankton under ultraviolet (UV) and photosynthetically available radiation (PAR) were investigated with the presence of hydroxycarboxylic acid (glucaric acid (GA), a model compound for organic acids excreted by phytoplankton). The incubation experiments were carried out on board using seawater samples collected in the location of the winter ice edge (WIE) and the spring ice edge (SIE) of the Southern Ocean. In this paper, we focus on the results of experiment in WIE. Throughout the experiments, dissolved Fe(II), major nutrients and in vivo fluorescence were monitored regularly. In addition, Chl-a, POC/PON, cell densities of phytoplankton and bacteria, bacterial production, organic peroxide, hydrogen peroxide and total CO2 were measured. The results from the WIE show that iron enrichment had a substantial effect on phytoplankton growth rate. Fe(III) addition in the presence of GA (FeGA) gave higher Fe(II) concentration and higher growth rate of phytoplankton than those in controls. Our results suggest that hydroxycarboxylic acid had a significant chemical and biological impact. The presence of GA influenced iron photochemistry and iron availability to phytoplankton. Phytoplankton growth responses to iron enrichments in incubations under UV and PAR were completely dissimilar. It seems that FeGA addition prominently changes the harmful effect of UV on the phytoplankton population. This study provides preliminary information on how the photoreduction of iron(III) and the phytoplankton growth are affected by iron enrichment in the presence of hydroxycarboxylic acid.
Keywords: Sørishavet; biokjemi; fotosyntese; marin biologi; oseanografi; phytoplankton

The diatom Fragilariopsis cylindrus and its potential as an indicator species for cold water rather than for sea ice - Quillfeldt von, Cecilie Hellum (Vie et Milieu / Life & Environment, 2004)
The importance of the diatom Fragilariopsis cylindrus (Grunow) Krieger in Helmcke & Krieger in the Arctic and Antarctic is well known. It is used as an indicator of sea ice when the paleoenvironment is being described. It is often among the dominant taxa in different sea ice communities, sometimes making an important contribution to a subsequent phytoplankton growth when released by ice melt. However, it may also dominate phytoplankton blooms in areas never experiencing sea ice. The use of F. cylindrus as an indicator for reconstruction of palaeoceanographic conditions is assessed from literature records. Its potential as an indicator species for sea ice appears to vary from region to region, but it is a good indicator of cold water.
Keywords: Sørishavet; diatomeer; marin biologi; paleoseanografi; phytoplankton; polarområdene

Light rather than iron controls photosynthate production and allocation in Southern Ocean phytoplankton populations during austral autumn - van Oijen, Tim; van Leeuwe, Maria A.; Granum, E.; Weissing, Franz J.; Bellerby, Richard G. J.; Gieskes, W. W. C.; de Baar, Hein J. W. (Journal of Plankton Research, 2004)
The role of iron and light in controlling photosynthate production and allocation in phytoplankton populations of the Atlantic sector of the Southern Ocean was investigated in April–May 1999. The 14C incorporation into five biochemical pools (glucan, amino acids, proteins, lipids and polysaccharides) was measured during iron/light perturbation experiments. The diurnal Chl a-specific rates of carbon incorporation into these pools did not change in response to iron addition, yet were decreased at 20 μmol photons m−2 s−1, an irradiance comparable with the one at 20–45 m in situ depth. This suggests that the low phytoplankton biomass encountered (0.1–0.6 μg Chl a L−1) was mainly caused by light limitation in the deep wind mixed layer (>40 m). Regional differences in Chl a-specific carbon incorporation rates were not found in spite of differences in phytoplankton species composition: at the Antarctic Polar Front, biomass was dominated by a diatom population of Fragilariopsis kerguelensis, whereas smaller cells, including chrysophytes, were relatively more abundant in the Antarctic Circumpolar Current beyond the influence of frontal systems. Because mixing was often in excess of 100 m in the latter region, diatom cells may have been unable to fulfil their characteristically high Fe demand at low average light conditions, and thus became co-limited by both resources. Using a model that describes the 14C incorporation, the consistency was shown between the dynamics in the glucan pool in the field experiments and in laboratory experiments with an Antarctic diatom, Chaetoceros brevis. The glucan respiration rate was almost twice as high during the dark phase as during the light phase, which is consistent with the role of glucan as a reserve supplying energy and carbon skeletons for continued protein synthesis during the night.
Keywords: Sørishavet; biokjemi; fotosyntese; fytoplankton; marin biologi; oseanografi; planteplankton

Metandania tordi, a new stegocephalid (Crustacea: Peracarida: Amphipoda) species from the Southern Ocean - Berge, Jørgen; Vader, Wim (Proceedings of the Biological Society of Washington, 2003)
A new stegocephalid (Amphipoda) species, Metandania tordi n.sp, is described, belonging to the subfamily Andaniexinae Berge & Vader 2001. The new species is the first record of the genus in the southern hemisphere. In addition, a morphological trait, previously not figured nor described within this family, is presented: a process proximally on the inner anterior surface of the fourth coxa. This locking-process is interpreted, and named accordingly, to enhance a relative stabilization of the third and fourth coxae. A brief comparison of the morphology of the fourth coxa between all five stegocephalid subfamilies is presented.
Keywords: Sørishavet; amfipoder; marin biologi; taksonomi

Contracted spleen in seals, estimates of dilated organs, and diving capacity - Cabanac, A. J. (Polar Biology, 2002)
The spleens of several seals from both the Arctic and the Antarctic were isolated and weighed when contracted. Spleens of the crabeater, leopard, and Weddell seals formed 0.23%, 0.39%, and 0.86% of the seals' body weights; those of the hooded and harp seals formed 0.56% and 0.35% of the seals' body weights. In these 5 phocids, a contracted spleen relates to the seal's body weight according to the equation (in which weights are in kilograms; n=26; r2=0.65): contracted spleen=0.006 (body weight)-0.11. Further, using the criterion reported in the literature that contracted spleens of hooded seal and harp seals weigh 80% less than when dilated, the sizes of dilated spleens were estimated for the 5 phocids of the study, plus that of the southern elephant seal. Dilated spleens ranged from 1 to 4% of the seal's body weight, which is in agreement with determinations of dilated spleens reported in the literature (harbor, 0.8–3.0%; harp, 1.5%; hooded, 2.2–4.0%). The general correlation among dilated spleens and the 6 phocids' body weights is: dilated spleen=0.026 (body weight)-0.39(where weights are in kilograms; n=31; r2=0.70). The size of the spleen (either contracted or dilated) from the different species of seals in this study appeared to be correlated with the diving capacity of the phocids, as given in the literature. The phocids with greater diving capacities are the ones with the larger spleens.
Keywords: NARE 1996/97; Sørishavet; Weddellhavet; marin biologi; pinnipedier; seler

Joint marine project during NARE 200/01: dissolved oxygen and nutrient tracers in the marine Norwegian sector of the Antarctic - Fransson, Agneta; Nøst, Ole Anders; Olsson, Kristina; O'Dwyer, Jane; Drange, Helge; Børsheim, Knut Yngve; Gammelsrød, Tor; Søreide, Janne; Karlsen, Tor Ivan; Jensen, Glen (Norwegian Antarctic Research Expedition (NARE) 2000/2001, 2002)
Keywords: NARE 2000/01; Sørishavet; biogeokjemi; ekspedisjoner; marin biologi; oseanografi

Annual export production in the interior Weddell Gyre estimated from a chemical mass balance of nutrients - Hoppema, Mario; de Baar, Hein J.W.; Bellerby, Richard G.J.; Fahrbach, Eberhard; Bakker, Karel (The Southern Ocean I: Climatic Changes in the Cycle of Carbon in the Southern Ocean, 2002)
Nitrate, phosphate and silicate data are presented from 1992 austral winter and 1998 austral autumn cruises with “FS Polarstern” in the Weddell Gyre. Because in the Weddell Gyre, away from the boundary current, the surface layer is eventually formed from upwelled deep water, the difference in nutrient concentrations between these layers can be used to compute net nutrient consumptions (identical with the export production). This method renders a value for the export production that is based on observed annual changes. The results are consistent for two years and two regions within the central gyre. The calculated net nitrate and phosphate consumptions were scaled to net carbon consumptions using canonical Redfield ratios, yielding 16–17μmolCkg−1yr−1. This equals 21±4gCm−2yr−1 as a robust estimate for the marginal ice zone. The net annual silicate consumption in the surface layer, which equals the export of biogenic silica, amounts to 15–18μmolkg−1yr−1. There is a tendency for higher values in the eastern Weddell Gyre. The estimated silicate consumption of about 1.8molSim−2yr−1 is relatively high compared to earlier estimations of biogenic silica export. The silicate to carbon consumption ratio of about 1 is very high, and documents the dominance of diatoms in the export of organic material. Résumé Sont présentées les distributions verticales de nitrate, de phosphate et de silicate en Mer de Weddell, pour les périodes de l’hiver austral 1992 et de l’automne austral 1998. Les eaux de surface du tourbillon à grande échelle de la Mer de Weddell (temps de résidence égal à 2.9 ans) sont formées par l’upwelling des eaux profondes. La différence de concentrations des sels nutritifs entre les couches profondes et de surface permettent de calculer la consommation annuelle, équivalente à la production exportée de l’élément nutritif considéré vers les couches profondes. Les résultats sont comparables pour les deux scénarios annuels étudiés. La production exportée de carbone pour les eaux de surface de la zone marginale de la glace, calculée à partir des consommations annuelles en nitrates et phosphates après transformation grâce aux rapports de Redfield, est estimée à 16–17μmolCkg−1yr−1 soit en moyenne 21±4gCm−2yr−1. La consommation annuelle de silicate est estimée à 1.8mol Si m−2yr−1, relativement élevée en comparaison des estimations antérieures. Le rapport molaire Si/C, voisin de 1 dans le matériel exporté, traduit la dominance des diatomées dans l’export de matières organiques.
Keywords: Sørishavet; Weddellhavet; fytoplankton; geofysikk; karbondioksid; marin biologi; oseanografi

Species richness of marine soft sediments - John, S Gray (Marine Ecology Progress Series, 2002)
Marine soft sediments comprise one of the largest and oldest habitats in the world, yet remarkably little is known about patterns of species richness. Here I present a short review of patterns of species richness and possible factors that influence such patterns. Species richness in general is remarkably high in both shallow coastal areas and the deep sea. However, there are clear differences the deep-sea has higher number of species for a given number of individuals than the coast. This can be explained by the larger amounts of primary production that reach coastal compared with deep-sea sediments, leading to higher numbers of individuals per unit area. Species density (the number of species per unit area) is also higher in the deep-sea than in coastal areas, but it is not obvious why this is so. Most studies of the broad patterns of species richness have used samples taken at small scales only. The problem with such analyses is that unless a large number of samples are taken, the true underlying pattern (or lack of it) may be wrongly interpreted. Recent studies have analysed species richness at larger scales. In general there seems to be a cline of increasing species richness from the Arctic to the tropics, but this is not the case in the southern hemisphere, where Antarctic species richness is high. However, it is not known whether high species richness in the Antarctic occurs at all spatial scales. To what extent these patterns are determined by evolutionary factors remains to be determined by the application of molecular methods. The available evidence suggests that environmental factors such as productivity, temperature, and sediment grain-size diversity play dominant roles in determining patterns of regional-scale species richness and patterns in species turnover, and it is probably the regional scale that primarily determines local species richness. KEYWORDS: Diversity · Deep sea · Coasts · Patterns · Scales
Keywords: Sørishavet; biodiversitet; marin biologi; polarområdene

Production and mortality of phytoplankton and sea-ice microalgae in the Southern ocean - Johnsen, Geir; Børsheim, Knut Yngve; Johansen, Torunn (Norwegian Antarctic Research Expedition (NARE) 2000/2001, 2002)
Keywords: Bouvetøya; NARE 2000/01; Sørishavet; alger; fytoplankton; havis; marin biologi; oseanografi; sjøis; zooplankton

Distribution and food consumption of Ross seals (Ommatophoca rossii) and Leopard seals (Hydrurga leptonyx) - Nordøy, Erling S; Blix, Arnoldus Schytte (Norwegian Antarctic Research Expedition (NARE) 2000/2001, 2002)
Keywords: NARE 2000/01; Sørishavet; havis; marin biologi; seler; sjøis; zoologi

Transport and transfer of organochlorines in the marine Norwegian Antarctic sector: field sampling programme during NARE 200/01 - Olsson, Kristina; Poltermann, Michael; Savinov, Vladimir; Vögele, Barbara; Kassobokova, Ksenia; Fransson, Agneta (Norwegian Antarctic Research Expedition (NARE) 2000/2001, 2002)
Keywords: NARE 2000/01; Sørishavet; marin biologi; oseanografi; plankton

Contribution of algal sinking and zooplankton grazing to downward flux in the Lazarev Sea (Southern Ocean) during the onset of phytoplankton bloom: a lagrangian study - Pakhomov, Evgeny A.; Froneman, Pierre W.; Wassmann, Paul; Ratkova, Tatjana; Arashkevich, Elena (Marine Ecology Progress Series, 2002)
ABSTRACT: Hydrography, chlorophyll a, phytoplankton and zooplankton dynamics and the vertical flux of particulate organic carbon (POC) and pigments in the upper 200 m were investigated for 12 consecutive days during a drogue study conducted in the open waters of the ice-edge zone of the Lazarev Sea during the austral summer (December/January) 1994/95. Results of the study indicate that during the experiment, primary production, although variable, increased from ~300 to ~800 mgC m-2d-1. This increase could likely be related to development of a shallow pycnocline. Analysis of sediment trap data showed that the vertical carbon flux resulting from sedimentation and grazing activity was greatest in the upper water column (<80 m). The importance of grazers to total POC flux was highest at the beginning and the end of the investigation and accounted for up to 15% of total carbon flux. The contribution of grazers to vertical flux was negligible (<2%) during the intermediate part of the Southern Ocean Drogue study. Lower contribution of grazers to sedimentation of POC at depth can likely be related to community composition of zooplankton. Sedimentation of phytoplankton cells from the upper water column increased during the study. Here, downward POC flux resulting from sedimentation of microphytoplankton was equivalent to 15-75% of the total. Increase in sedimentation of phytoplankton during the study can be related to an increase in the average size of phytoplankton cells. Transport of POC from surface waters to deeper depths resulting from sedimentation or grazing activity was equivalent to <48% of total daily primary production, measured at 50 m, while the same value for phytoplankton flux did not exceed 27% of the total. Zooplankton density was insufficient to exert either a positive (via faecal pellets) or negative (via reducing suspended phytoplankton concentration) effect on particulate carbon sedimentation. This resulted in algal sink being the most important mechanism in downward POC flux during the onset of the phytoplankton bloom period in the Marginal Ice Zone, even in the presence of pelagic tunicates.
Keywords: Sørishavet; alger; biokjemi; marin biologi; oseanografi; phytoplankton; zooplankton

Seaweeds in Cold Seas: Evolution and Carbon Acquisition - Raven, John A.; Johnston, Andrew M.; Kübler, Janet E.; Korb, Rebecca; Mcinroy, Shona G.; Handley, Linda L.; Scrimgeour, Charlie M.; Walker, Diana I.; Beardall, John; Clayton, Margaret M.; Vanderklift, Mathew; Fredriksen, Stein; et al. (Annals of Botany, 2002)
Much evidence suggests that life originated in hydrothermal habitats, and for much of the time since the origin of cyanobacteria (at least 2·5 Ga ago) and of eukaryotic algae (at least 2·1 Ga ago) the average sea surface and land surface temperatures were higher than they are today. However, there have been at least four significant glacial episodes prior to the Pleistocene glaciations. Two of these (approx. 2·1 and 0·7 Ga ago) may have involved a ‘Snowball Earth’ with a very great impact on the algae (sensu lato) of the time (cyanobacteria, Chlorophyta and Rhodophyta) and especially those that were adapted to warm habitats. By contrast, it is possible that heterokont, dinophyte and haptophyte phototrophs only evolved after the Carboniferous–Permian ice age (approx. 250 Ma ago) and so did not encounter low (≤5 °C) sea surface temperatures until the Antarctic cooled some 15 Ma ago. Despite this, many of the dominant macroalgae in cooler seas today are (heterokont) brown algae, and many laminarians cannot reproduce at temperatures above 18–25 °C. By contrast to plants in the aerial environment, photosynthetic structures in water are at essentially the same temperature as the fluid medium. The impact of low temperatures on photosynthesis by marine macrophytes is predicted to favour diffusive CO2 entry rather than a CO2‐concentrating mechanism. Some evidence favours this suggestion, but more data are needed.
Keywords: Sørishavet; alger; biogeografi; botanikk; makroalger; marin biologi

Norwegian Antarctic Research Expedition (NARE) 2000/2001 - Winther, Jan-Gunnar (ed.) (Norsk Polarinstitutt, 2002)
Keywords: Dronning Maud Land; biologi; ekspedisjoner; forskning; geodesi; glasiologi; logistikk; marin biologi; miljøvern; naturressurser

Antarctic marine benthic biodiversity in a world-wide latitudinal context - Gray, John S. (Polar Biology, 2001)
In the 1950s and 1960s, the first data sets were assembled to examine whether or not there was a latitudinal gradient of species richness in the sea. These data comprised very few species and were from very small areas. However, recent data from large species lists covering broad geographical ranges suggest strongly that there is a gradient of increasing species richness from the Arctic to the tropics. However, the Southern Ocean has high species richness and in the southern hemisphere there is no clear evidence of a cline of increasing richness from pole to tropic. The great richness of the Southern Ocean compared with the Arctic is probably due to its great age, the fact that it covers a much larger area and that it has higher structural heterogeneity formed by living organisms. The importance of area as a determinant of species richness needs to be studied in more detail since most studies have been confined to small areas. A number of hypotheses have been proposed to explain the species:area relationship and these are discussed. An alternative explanation for the latitudinal cline in the northern hemisphere is the energy-input hypothesis, but again this has not been adequately tested. Two studies on the relationship between local and regional species richness show a significant positive correlation. These findings suggest that local assemblages are not tightly organised and saturated with species but are open to recruitment from the regional species pool. Whether or not such a relationship holds in Antarctica is unknown. It is concluded that further studies of the Southern Ocean are likely to provide new findings fundamental to the "new" discipline of macroecology, which examines patterns and processes at the geographic scale.
Keywords: Sørishavet; bentiske organismer; bentos; biodiversitet; marin biologi; økologi

Counts of southern elephant seals, Mirounga leonina, at Bouvet Island - Kirkman, S. P.; Hofmeyr, G. J. G.; Bester, M. N.; Isaksen, K. (Polar Biology, 2001)
Southern elephant seals were counted and classified into subjective sex-age classes on a weekly basis during expeditions to Bouvet Island in the austral summers of 1996/1997 and 1998/1999. The expeditions coincided with the moulting period of elephant seals aged one year and older. The presence of weaned pups at the principal haulout site, Nyrøysa/Westwindstranda, during the latter expedition, indicates that breeding took place here during 1998. Elephant seal counts from previous expeditions are summarised.
Keywords: Bouvetøya; NARE 1996/97; NARE 1998/99; marin biologi; pinnipedier; seler

Phytoplankton dynamics at the ice-edge zone of the Lazarev Sea (Southern Ocean) during the austral summer 1994/1995 drogue study - Pakhomov, Evgeny; Ratkova, Tatjana; Froneman, Pierre W.; Wassmann, Paul (Polar Biology, 2001)
Phytoplankton dynamics in the open waters of the ice-edge zone of the Lazarev Sea were investigated over 12 consecutive days during a drogue study conducted in austral summer (December/January) 1994/1995. Throughout the study, the upper water column (<30 m) was stratified with a well-defined pycnocline evident. Although a subsurface intrusion of colder, more saline water into the region was recorded on days 5–9 of the experiment, its effect on the water column structure was negligible. Total surface chlorophyll a biomass doubled between days 1 and 5 (from 0.82 to 1.62 mg m–3), and then showed a tendency to stabilise, while the depth-integrated chlorophyll a standing stock displayed an increasing trend during the entire experiment. All changes in biomass were associated with an increase in microphytoplankton. Flagellates and picoplankton dominated cell counts, while diatoms composed most of the phytoplankton biovolume. Results of the study indicate that, during the period of investigation, average cell abundance decreased. Coupled with this decrease was an increase in the biovolume and average size of the phytoplankton. Phytoplankton succession was observed in the ice edge during the drogue study. Typical ice-associated species of genera Haslea, Fragilariopsis and Chaetoceros, which dominated at the beginning of study, were replaced by open-water species of genera Corethron, Dactyliosolen and Rhizosolenia. The shift in phytoplankton species composition and size can likely be related to high light intensities and grazing by microzooplankton. The intrusion of colder, more saline water on day 5 appeared to modify the diatom succession, indicating extreme variability in phytoplankton dynamics in the near ice-edge zone of the Lazarev Sea.
Keywords: Sørishavet; fytoplankton; marin biologi; oseanografi

Lipids, trophic relationships, and biodiversity in Arctic and Antarctic krill - Falk-Petersen, Stig; Hagen, Wilhelm; Kattner, Gerhard; Clarke, Andrew; Sargent, John (Canadian Journal of Fisheries and Aquatic Sciences, 2000)
Environmental seasonality is a critical factor in structuring polar marine ecosystems. The extensive data now available on the lipids of Arctic and Antarctic euphausiids show that all species are characterised by a seasonally high lipid content, and neutral lipids, whether wax esters or triacylglycerols, are primarily accumulated for reproduction. The Arctic Thysanoessa inermis and the Antarctic Euphausia crystallorophias contain high levels of wax esters and higher concentrations of 18:4(n-3) and 20:5(n-3) and a lower ratio of 18:1(n-9)/(n-7) fatty acids in their neutral lipids than the Arctic Thysanoessa raschii and the Antarctic Thysanoessa macrura and Euphausia superba. Large amounts of phytol in the lipids of T. raschii and E. crystallorophias during winter suggest the ingestion of decaying algae originating in sedimenting material or in sea ice. Thysanoessa raschii, T. macrura, and E. superba have a high ratio of 18:1(n-9)/ (n-7) fatty acids, indicating animal carnivory. We conclude that T. inermis and E. crystallorophias are true high polar herbivores, while T. raschii, T. macrura, and E. superba are omnivores with a more boreal distribution. The Arctic species Thysanoessa longicaudata and Meganyctiphanes norvegica are carnivores feeding on Calanus, as indicated by high amounts of 20:1(n-9) and 22:1(n-11) fatty acids.
Keywords: Antarktis; biodiversitet; copepoder; krill; marin biologi; marine økosystemer; plankton

Diet and estimated food consumption of Antarctic fur seals at Bouvetøya during summer - Kirkman, Stephen; Wilson, W.; Klages, Norbert; Bester, Marthán; Isaksen, Kjell (Polar Biology, 2000)
Collection and analysis of natural regurgitations and fresh scats, deposited by Antarctic fur seals at the Nyrøysa colony, Bouvetøya, during December 1998 to February 1999, afforded a comprehensive description of the dietary composition of this expanding population during the summer months. Mature, adult Euphausia superba was the staple diet of fur seals at Nyrøysa, while squid and myctophid fish appeared to be taken opportunistically. In metric tons, the total Bouvetøya fur seal population is estimated to have consumed a minimum of 14,365 t krill (representing 1.2713 × 1010 individuals of 1.13 g mass), 186 t fish, 184 t squid and 14,735 t over 3 months, but there are many possible sources of error in these estimates. It is presumed that over-indulgence in krill may cause animals to regurgitate ashore.
Keywords: Bouvetøya; marin biologi; pelsseler; pinnipedier; seler; zoologi

Postsealing genetic variation and population structure of two species of fur seal (Arctocephalus gazella and A. tropicalis) - Wynen, Louise P.; Goldsworthy, Simon D.; Guinet, Christophe; Bester, Marthán N.; Boyd, Ian L.; Gjertz, Ian; Hofmeyr, Greg J. G.; White, Robert W. G.; Slade, Rob (Molecular Ecology, 2000)
Abstract Commercial sealing in the 18th and 19th centuries had a major impact on the Antarctic and subantarctic fur seal populations (Arctocephalus gazella and A. tropicalis) in the Southern Ocean. The intensive and unrestricted nature of the industry ensured substantial reductions in population sizes and resulted in both species becoming locally extinct at some sites. However, both species are continuing to recover, through the recolonization of islands across their former range and increasing population size. This study investigated the extent and pattern of genetic variation in each species to examine the hypothesis that higher levels of historic sealing in A. gazella have resulted in a greater loss of genetic variability and population structure compared with A. tropicalis. A 316-bp section of the mitochondrial control region was sequenced and revealed nucleotide diversities of 3.2% and 4.8% for A. gazella and A. tropicalis, respectively. There was no geographical distribution of lineages observed within either species, although the respective ΦST values of 0.074 and 0.19 were significantly greater than zero. These data indicate low levels of population structure in A. gazella and relatively high levels in A. tropicalis. Additional samples screened with restriction endonucleases were incorporated, and the distribution of restriction fragment length polymorphism (RFLP) and sequence haplotypes were examined to identify the main source populations of newly recolonized islands. For A. tropicalis, the data suggest that Macquarie Island and Iles Crozet were probably recolonized by females from Marion Island, and to a lesser extent Ile Amsterdam. Although there was less population structure within A. gazella, there were two geographical regions identified: a western region containing the populations of South Georgia and Bouvet?ya, which were the probable sources for populations at Marion, the South Shetland and Heard Islands; and an eastern region containing the panmictic populations of Iles Kerguelen and Macquarie Island. The latter region may be a result of a pronounced founder effect, or represent a remnant population that survived sealing at Iles Kerguelen.
Keywords: Bouvetøya; Sørishavet; genetikk; marin biologi; pinnipedier; seler